APPLICATION OF THE COBB-DOUGLASS PRODUCTION FUNCTION FUNCTION TO MSMES AND LARGE BUSINESSES IN STIMULATING THE NATIONAL INCOME OF MSMES AND LARGE BUSINESSES DURING THE PANDEMIC (2015-2019) - Sofie Sofie (Jurnal Scientia, 2023)
This study aims to find out application of the cobb-douglass production function function to msmes and large businesses in stimulating the national income of msmes and large businesses during the pandemic (2015-2019). The type of research used is quantitative research with hypothesis testing which aims to test the influence of the number of MSME and UB business units as well as the number of workers from MSMEs and UB on the national income of MSMEs and UB using a panel regression model. The results of this study state that In all business units, it is proven that the number of business units has a significant positive effect on the GDP of MSMEs and UB. The influence of labor both as a whole and according to the type of business does not have a significant effect on the GDP of MSMEs and UB. The elasticity of the number of business units positively affects the GDP of MSMEs both as a whole and according to the business unit group. For the overall homogeneity level is in an increasing return to scale condition and according to the group of business units, Micro, Small and Large businesses are in a condition of increasing return to scale, while for the Middle group are in a decreasing return to scale condition. For production intensity, overall and according to business unit groups, no production process in MSMEs and UB focuses on using certain inputs as the dominant input